Pressure, Performance and Prestige: Dilemmas for Contemporary Professionals - Lemos, Ana Heloisa Costa; Gottlieb, Leila Sharon Nasajon; Costa, Alessandra de Sá Mello da (Organizações & Sociedade, 2016)
Recent changes in the world of work have resulted in a greater level of work intensification. Whilst there have been gains in productivity, workers have been subject to increasing demands of both a physical and mental nature, which tend to have a negative impact on their well-being. Our interest in understanding this phenomenon has led to a qualitative study that seeks to analyse the experiences of professional graduates working in organizations that use high- performance practices, which tend to generate work intensification. The respondents revealed both the negative implications of work intensification, such as an increase in the working day, excessive pressure and sacrifices in their personal lives, as well as other aspects considered positive, such as learning, professional growth, autonomy and financial gains. These latter aspects deserve attention, since they can help us understand what leads qualified workers to accept intensified working practices.